2012
DOI: 10.1111/j.1365-2796.2012.02542.x
|View full text |Cite
|
Sign up to set email alerts
|

Excessively high soluble Klotho in patients with acromegaly

Abstract: Objectives. Klotho-deficient mice develop a syndrome resembling accelerated ageing, and genetic variants of Klotho have been associated with human ageing. In humans, serum levels of soluble Klotho decrease with age and with chronic renal failure. The aim of our study was to examine the relationship between excess growth hormone (GH) and serum levels of Klotho in patients with acromegaly, a disease usually caused by a pituitary adenoma, which is associated with high phosphate levels and reduced life expectancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 25 publications
8
64
0
3
Order By: Relevance
“…Our present study confirms the earlier findings of highly significant difference in sKlotho levels in patients with active acromegaly to other groups [11][12][13]. The difference was statistically significant when we compared the AA group to the SCA and WCA groups as well as to the CG group, so it was independent of methods of therapy or health conditions.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our present study confirms the earlier findings of highly significant difference in sKlotho levels in patients with active acromegaly to other groups [11][12][13]. The difference was statistically significant when we compared the AA group to the SCA and WCA groups as well as to the CG group, so it was independent of methods of therapy or health conditions.…”
Section: Discussionsupporting
confidence: 81%
“…It is known that in acromegaly there are high levels of FGF-23, phosphate, and calcitriol and also FGF-23 resistance [13][14]16]. On the other hand, it was shown that the high level of sKlotho is a consequence of increased pituitary GH secretion, and higher pituitary transmembrane Klotho expression was not observed [7,12] . The aim of our case-control study was to assess the serum levels of soluble a-Klotho in acromegalic patients in relation to the activity of disease and to compare it with the control group (CG).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…We recently found that serum-soluble aKL is markedly elevated in patients with acromegaly and that this aKL excess reversed following adenoma removal (22). In order to assess whether high serum levels of soluble aKL are specific to patients with GH-producing pituitary adenomas, we now present a prospective controlled study that documents the baseline serum levels of aKL in patients with acromegaly compared with a control group of patients with other pituitary adenomas.…”
Section: Introductionmentioning
confidence: 99%